The influence of employees’ cross-cultural psychological capital on workplace psychological well-being - Martina Kotze; Liezel Massyn (SA Journal of Industrial Psychology, 2019)
Orientation: In order to withstand the global and local cultural diversity and challenges that South African workplaces face, it is essential for employees to have cross-cultural psychological resources (i.e. cross-cultural psychological capital). A lack of cross-cultural psychological capital or the inability to adjust to cross-cultural environments may impact negatively employees’ psychological well-being. Research purpose: The purpose of this research was to explore the influence of employees’ cross-cultural psychological capital on their psychological well-being (indicated by burnout and work engagement). Motivation for the study: Cross-cultural psychological capital and its influence on employees’ psychological well-being have not been explored in South Africa. This study aimed to fill this gap. Research approach/design and method: Data were collected using questionnaires completed by 213 employees from different organisations in South Africa. Partial least squares (PLS) and structural equations modelling (SEM) were used to explore the relationships between the independent variable (cross-cultural psychological capital) and burnout and work engagement. Main findings: Cross-cultural psychological capital had a statistically significant negative influence on burnout and a statistically significant positive influence on work engagement. It had a stronger negative influence on emotional exhaustion than on cynicism and a stronger positive influence on vigour than on dedication. Practical/managerial implications: Enhancing employees’ cross-cultural psychological capital by means of programmes and short interventions may improve their psychological well-being. Contribution/value-add: This research contributed to filling the gap in the literature regarding the role of cross-cultural psychological capital in the psychological well-being of employees working in cross-cultural environments.